Adjektiva Bahasa Ngalum - Siti Masitha Iribaram (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2015)
Ngalum language is one of local language whose large native speaker in Papua Province. Ngalum language is spoken by Ngalum tribes who live in Oksibil valley, Okisop valley, and Okbon valley of Pegunungan Bintang Regency. Ngalum language has some word classes as like other languages in the world. One of them is adjective. in this article, adjective of Ngalum language is based on adjective of Bahasa Indonesia from its semantical behavior. This writing used three stages of descriptive method. They are, collecting data stage, analyzing data stage and presenting the result of the data analysis. Data, in this writing, was collected using interview method (metode cakap) through stimulation technique (teknik pancing) as a basic technique while face-to-face interview (cakap semuka) and noting technique (teknik catat) as advanced techniques. Thus, data analyzing used distributional method. There are two main types of adjective, namely, adjective of quality and adjective of quantity. Adjective of quality, which explores about quality of a noun, consist of (1) opinion as adjective, (2) size as adjective, (3) colour as adjective, (4) time/age as adjective, (5) space as adjective, (6) feeling as adjective , and (7) sense as adjective. While, adjective of quantity explores about a membership of a noun in a group